Similar Impact of Psoriatic Arthritis and Rheumatoid Arthritis on Objective and Subjective Parameters of Hand Function - Liphardt, Anna-Maria; Manger, Eva; Liehr, Sonja; Bieniek, Lisa Maria; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ACR Open Rheumatology, 2020)
ObjectiveThe objective of this study was to compare the impact of psoriatic disease (psoriatic arthritis [PsA] and psoriasis) and rheumatoid arthritis (RA) on objective and subjective parameters of hand function.
CRIS-Team WoS Importer:2021-07-16